2017
DOI: 10.1007/s40843-017-9042-0
|View full text |Cite
|
Sign up to set email alerts
|

Highly active CeO2 hollow-shell spheres with Al doping

Abstract: Metal oxide hollow structures are of great interest in many current and emerging areas of technology. This paper presents a facile and controlled protocol for the synthesis of Al-doped CeO2 hollow-shell spheres (CHS), where the dopant confers enhanced stability and activity to the material. These Al-doped CeO2 hollow-shell spheres (ACHS) possess a controllable shell number of up to three, where the sizes of the exterior, middle, and interior spheres were about 250-100 nm,150-50 nm, and 40-10 nm, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Compared with mesoporous structures, HoMSs have more internal cavities that are arranged in order so that sequential catalysis or sequential release can be realized. Therefore, HoMSs are expected to have better performances over their single‐ or double‐shelled counterparts and other ordinary porous structures or nanostructures for applications such as electrochemical energy storage, solar energy conversion, electromagnetic wave absorption, catalysis, and drug delivery …”
Section: Introductionmentioning
confidence: 99%
“…Compared with mesoporous structures, HoMSs have more internal cavities that are arranged in order so that sequential catalysis or sequential release can be realized. Therefore, HoMSs are expected to have better performances over their single‐ or double‐shelled counterparts and other ordinary porous structures or nanostructures for applications such as electrochemical energy storage, solar energy conversion, electromagnetic wave absorption, catalysis, and drug delivery …”
Section: Introductionmentioning
confidence: 99%
“…The generation/elimination of oxygen vacancies, together with the corresponding alteration of valence state of Ce, leads to the widely-recognized oxygen storage capacity (OSC) that makes CeO 2 a highlight in catalysis research [1][2][3][4], and applications like photocatalysis and solid oxide fuel cells that significantly rely on the amount and mobility/ diffusion of carriers, such as light absorption and band structure, while the generation of defects can be beneficial by inducing more carriers [5][6][7][8][9]. Thus, tailoring composition and morphology of pure and doped ceria has been a highlight in catalyst and electrolyte research [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…As we know, the loss of an oxygen atom from Cu 2 O and CuO generates an oxygen vacancy. Surface oxygen vacancies are the most relevant surface defects in metal oxides, and they participate in a large number of chemical reactions [35,50]. Although the exact mechanism of Rochow reaction over Cu-based catalysts is still unclear, previous studies have shown that CH 3 Cl first adsorbs on the surface to form Cu x Si active phase, then reacts with Si atoms to form M2 [26,30,33,49].…”
Section: Science China Materialsmentioning
confidence: 99%